Mobile Learning Dalam Pembelajaran Interaktif Untuk Anak Usia Dini Menggunakan Metode STEAM - Teguh Setiadi; Laksamana Rajendra Haidar (Teknik Komputer Politeknik Negeri Sriwijaya, 2021)
Technology is very helpful for simplifying work and daily needs and provides a variety of entertainment for those who want it. For this reason, the community is required to make a change in every activity. The teacher's learning process at Tunas Harapan Kindergarten, which is located at Limbangan Village Rt 02 Rw 04 Banyu Putih District, uses paper media that is attached to the wall or uses teaching aids in delivering learning materials that have not used learning technology. Thus, children feel bored and sometimes neglect to pay attention to the teacher's explanation, and sometimes the learning process is very dependent on the delivery of material delivered by the teacher directly. For this reason, providing support for interactive learning is to take advantage of the existence of media learning facilities that use technology-based mobile education. The application of the learning model with the STEAM method in the learning activities of children aged 5 to 6 years, one of which is the development of student creativity. In building mobile education in interactive learning for early childhood to present or introduce mobile-based education technology to children from an early age, in independent learning it is easily accessible outside class hours and assisting teachers in teaching in particular. Keywords— Mobile Education, Interactive learning, STEAM method